Clinical profile and early hospital outcome of late preterms admitted in a tertiary care neonatal unit from South India - NR, Ezhilvannan; HN, Vani; HS, Niranjan; Benakappa, Naveen (International Journal of Contemporary Pediatrics, 2017)
Background: Late preterm infants refer to those born between 34 completed weeks (340/7) and less than 37 completed weeks (366/7). The incidence of medical problems, either short-term or long-term, is higher among late preterm infants than term infants. Methods: This is prospective observational study conducted in Indira Gandhi Institute of Child Health, which is a tertiary care pediatric hospital, which caters to only outborn. All late preterm babies admitted, who met the inclusion criteria were studied for a period of one year from September 2012 to august 2013. After taking consent from parents, detailed antenatal history were taken in a structured proforma. Short term outcome was assessed in the form of neonatal morbidities, mortality. These late preterm infants were followed up and readmission to hospital and reasons for readmission were evaluated. Results: A total of one hundred and forty four late preterm neonates comprised the study group. Male preponderance was noticed with a ratio of 1.5:1. Majority of the neonates had birth weight more than 2 kg. Premature rupture of membrane and previous history of caesarian section formed the major maternal risk factor for preterm. Neonatal hyperbilirubinemia was the major morbidity followed by respiratory distress, sepsis and feed intolerance. Majority of late preterm neonates required more than 7 days of hospital stay. Rate of rehospitalisation were also high among late preterm. Conclusions: Late preterm infant group is less studied group. Morbidity and mortality in them is higher than expected, hence they need special attention while in hospital and a better follow up protocol after discharge. Late preterm infants comprise the majority of preterm newborns, caring for such a large population who are prone to have unfavourable outcomes can exert a profound impact on the society.